Vers une éducation à la sobriété numérique - Sarah Descamps; Gaëtan Temperman; Bruno De Lièvre (Humanités Numériques, 2022)
The ecological transition and the digital transition have given rise to a new societal challenge: digital sustainability. This issue is at the crossroads of digital humanities and environmental sciences and consists in understanding our technological impacts on the environment and moderating them. In fact, the digital pollution is currently 4% and by 2023 this percentage will have doubled. The ambition of this article is for education to grasp this tension and initiate an education to digital sustainability. Starting from the observation that digital natives can be the source of a sustainable transformation and of the diffusion of eco-responsible actions, we will try to conceptualise this new competence of the 21st century, which can be organised in three dimensions: understanding the impact of TIC, identifying digital solutions to protect the environment and using technologies responsibly.